Terrorism vulnerability assessment in Java Island: a spatial multi-criteria analysis approach - Asep Adang Supriyadi; Masita Dwi Mandini Manessa (Indonesian Journal of Geography, 2020)
Terrorism is one of the Indonesia’s national security threat. The attack mostly happens in Java Island, attracted by the dense population, also because the island is a center for economic and governance. The spatial pattern of terrorism attack shows correlations with the spatial density of the targeted attack. Therefore, this study assesses the spatial vulnerability of Java Island using a spatial multi-criteria analysis (SMCA). The main attributes analyzed were the density of the past terrorist attack, arrested area, police/military facility, government facility, business center, densely populated area, and church, determine that in the case of a terrorist attack is strongly affected by the attraction of the area.